A method for preparing an iridium oxide @ ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water
By enriching oxygen-containing functional groups on the surface of RuO2 precursor and controlling the thickness of the IrO2 coating layer, an iridium oxide@ruthenium oxide composite catalyst was prepared, which solved the problems of traditional catalysts being deactivated under high oxidation potential and scarcity of Ir elements, realizing the High catalytic activity and low cost effects.
Patent Information
- Application Number
- CN202211318265.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-10-26
AI Technical Summary
In the existing PEM water electrolysis technology, the selection of oxygen precipitation reaction (OER) catalysts are mainly limited to metal oxides. Traditional catalysts are prone to inactivate under high oxidation potentials, and the Ir element is scarce and expensive, which increases costs.
Using the preparation method of iridium oxide @ ruthenium oxide composite catalyst, oxygen-containing functional groups are enriched on the surface of RuO2 precursor by introducing ozone and controlling heating conditions, quickly anchoring the Ir salt complex, and controlling the thickness of the IrO2 cladding layer, and preparing Evenly distributed core-shell nanocomposite catalyst.
The catalytic activity is better than that of the IrO2 catalyst, reducing the amount of metal Ir used by more than half, and the catalyst has good chemical durability and electrochemical activity.
Smart Images

Figure CN115747857B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by water electrolysis, and specifically relates to a method for preparing an iridium oxide@ruthenium oxide composite catalyst suitable for oxygen separation by acidic water electrolysis. Background Art
[0002] Hydrogen is a carrier of clean energy. It can be produced from traditional fossil fuels such as coal, oil, and natural gas, as well as from clean energy such as wind and solar energy. Hydrogen energy obtained from renewable energy is considered "green hydrogen". Among them, water electrolysis hydrogen production technology is particularly important. Currently, mature water electrolysis technologies include: alkaline water electrolysis, solid oxide electrolyzer, and proton exchange membrane (PEM) water electrolysis. Among them, the PEM technology route has the advantages of compact structure, high current density, fast startup response, small footprint (portable), and suitable temperature range (20-80 C°). In addition, PEM hydrogen production technology is very suitable for linkage with green renewable energy such as wind and solar energy to convert "abandoned electricity" into chemical energy for storage.
[0003] Water electrolysis mainly involves two half-reaction processes, the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Among them, OER is the main bottleneck restricting its performance. The slow kinetic process of OER requires a higher overpotential at the anode to overcome the reaction energy barrier, so the main energy loss in PEM water electrolysis comes from the high potential of the anode. The reaction path of OER usually involves the adsorption and desorption process of *O, *OH, and *OOH intermediates, which involves a multi-step multi-electron transfer process. Traditional transition metal catalysts are easily deactivated at high oxidation potentials, so the choice of OER catalysts is mainly limited to metal oxides. In addition, due to the participation of lattice oxygen in the reaction of some metal oxides, there is also a coupled transfer process of OO. Although it can effectively reduce the energy barrier of the reaction, the participation of lattice oxygen will also lead to the collapse of the catalyst structure, resulting in the attenuation of catalytic activity and durability.
[0004] So far, IrO2 and RuO2 are the catalysts with the best OER performance. Among them, RuO2 has excellent activity under acidic conditions, but it is more easily oxidized to cause the structural collapse of the catalyst, resulting in the dissolution of the catalyst and the reduction of catalytic activity. IrO2 can maintain good catalytic activity while having good stability. However, the reserves of Ir element on the earth are scarce and expensive, which increases the cost of PEM water electrolysis. Therefore, it is urgent to find cheap, easy to prepare, high catalytic activity and good stability alternative materials to reduce the cost of PEM water electrolysis. Summary of the invention
[0005] In view of the defects of the prior art, the present invention provides a method for preparing an iridium oxide@ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water, which can prepare an iridium oxide-coated ruthenium oxide core-shell nanocomposite catalyst with uniform phase distribution, good catalytic activity and long chemical durability.
[0006] A method for preparing an iridium oxide@ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water comprises the following steps:
[0007] (1) Prepare RuCl3 solution with concentrated hydrochloric acid, dilute with water, heat the diluted solution to 80-100°C, then add NaOH solution to adjust the pH to 8-9; introduce ozone into the solution under stirring; then add hydrochloric acid to adjust the pH to 6-7, and let stand for 0.5-1h to obtain solution A;
[0008] (2) While stirring, add iridium salt solution dropwise to solution A, continue stirring at 80-100°C for 1-2 hours and add ammonia water to adjust the pH to 12; let stand until the solution is completely precipitated, separate the precipitate and the supernatant, and dry the precipitate to obtain a precursor;
[0009] (3) Calcine the precursor, cool it, wash it, filter it, and freeze-dry it.
[0010] Preferably, in step (1), the concentration of ruthenium in the RuCl3 solution is 0.01-0.1 g / mL.
[0011] Preferably, the concentration of ozone is 30%, the flow rate is 50 sccm, and the ozone introduction time is 0.5-1 h.
[0012] Preferably, in step (2), the iridium salt solution is added in a molar ratio of iridium to ruthenium of 1:(1-5).
[0013] Preferably, the concentration of iridium in the iridium salt solution is 0.01-0.1 g / mL.
[0014] Preferably, the iridium salt is iridium trichloride, iridium tetrachloride, chloroiridic acid, ammonium chloroiridate, iridium acetate or potassium hexachloroiridate.
[0015] Preferably, the drying condition in step (2) is drying at 60-70° C. for 2.5-3 h.
[0016] Preferably, the calcination conditions in step (3) are calcination at 300-700° C. for 3-5 hours.
[0017] Preferably, the cleaning in step (3) is first performed with 0.1-0.5 mol / L dilute hydrochloric acid, and then with water until no chloride ions are present in the cleaning solution.
[0018] Advantages of the present invention:
[0019] (1) The preparation method of the IrO2@RuO2 catalyst provided by the present invention is to continuously introduce ozone, so that a variety of oxygen-containing functional groups are enriched on the surface of the RuO2 precursor particles under heating conditions. The presence of oxygen-containing functional groups can quickly anchor the Ir salt complex. By controlling the pH value of the added ammonia water and the added content of Ir, the thickness of the IrO2 coating layer can be accurately controlled, and the IrO2@RuO2 composite catalyst is effectively prepared, avoiding the problem of catalyst particles being too large and the morphology being difficult to control in the prior art;
[0020] (2) The IrO2@RuO2 composite catalyst prepared by the present invention has a good BET specific surface area and can reach a current density of 10 mAcm -2 The oxygen evolution potential is 285-300 mV, and the catalytic activity is better than that of IrO2 catalyst at the same current density, reducing the amount of metal Ir by more than half. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 SEM spectrum of the catalyst prepared in Example 2;
[0022] Figure 2 TEM spectrum of the catalyst prepared in Example 2;
[0023] Figure 3 N2 isothermal absorption / desorption curve of the catalyst prepared in Example 2;
[0024] Figure 4 The pore size data distribution diagram of the catalyst prepared in Example 2;
[0025] Figure 5 Electrochemical impedance spectra of the catalyst prepared in Example 2 and the comparative example IrO2 catalyst;
[0026] Figure 6 Polarization current curves of the catalysts prepared in Examples 1-3 and the comparative example IrO2 catalyst;
[0027] Figure 7 Double layer capacitance values of the catalyst prepared in Example 2 and the comparative example IrO2 catalyst. DETAILED DESCRIPTION
[0028] Example 1
[0029] A method for preparing an iridium oxide@ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water comprises the following steps:
[0030] (1) Use 36wt% concentrated hydrochloric acid to prepare RuCl3 into a RuCl3 solution with a ruthenium concentration of 0.01g / mL. Take 10mL of the RuCl3 solution and add 90mL of water to dilute it. Heat the diluted solution to 90℃, then add 1mol / L NaOH solution to it. Black flocculent precipitates gradually appear in the solution. Continue to add NaOH solution to adjust the pH to 8. Under stirring conditions, introduce 30% ozone for 1h at an ozone flow rate of 50sccm. Then add 1mol / L hydrochloric acid solution to it to adjust the pH to 6. Let it stand for 0.5h to obtain solution A.
[0031] (2) Under stirring, add 10 mL of IrCl4 solution with an iridium concentration of 0.01 g / mL to solution A, stir at 90°C for 2 h, and add ammonia water to adjust the pH to 12; let stand for 5 h, the solution is completely precipitated, separate the precipitate and the supernatant, and dry the precipitate at 60°C for 3 h to obtain a precursor;
[0032] (3) Place the precursor in a muffle furnace, heat to 300°C at a heating rate of 5°C / min, and calcine at 300°C for 3 h. After cooling, wash with 0.1 mol / L dilute hydrochloric acid and then with deionized water until there is no chloride ion in the washing solution, filter, and freeze-dry.
[0033] Example 2
[0034] In step (3), the mixture is heated to 400° C. and calcined at 400° C. for 3 h. The rest is the same as in Example 1.
[0035] Example 3
[0036] In step (3), the mixture is heated to 500° C. and calcined at 500° C. for 3 h. The rest is the same as in Example 1.
[0037] Example 4
[0038] A method for preparing an iridium oxide@ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water comprises the following steps:
[0039] (1) Use 36wt% concentrated hydrochloric acid to prepare RuCl3 into a RuCl3 solution with a ruthenium concentration of 0.1g / mL. Take 10mL of 0.1g / mL RuCl3 solution and add 90mL of water to dilute it. Heat the diluted solution to 80°C, then add 1mol / L NaOH solution to it. Black flocculent precipitates gradually appear in the solution. Continue to add NaOH solution to adjust the pH to 9. Under stirring conditions, introduce 30% ozone for 0.5h at an ozone flow rate of 50 sccm. Then add 1mol / L hydrochloric acid solution to it to adjust the pH to 7. Let it stand for 1h to obtain solution A.
[0040] (2) Under stirring, add 20 mL of IrCl4 solution with an iridium concentration of 0.1 g / mL to solution A, stir at 80°C for 1 h and add ammonia water to adjust the pH to 12; let stand for 5 h until the solution is completely precipitated, separate the precipitate and the supernatant, and dry the precipitate at 70°C for 2.5 h to obtain a precursor;
[0041] (3) Place the precursor in a muffle furnace, heat to 700°C at a heating rate of 5°C / min, and calcine at 700°C for 3 h. After cooling, wash with 0.5 mol / L dilute hydrochloric acid and then with deionized water until there is no chloride ion in the washing solution, filter, and freeze-dry.
[0042] Example 5
[0043] A method for preparing an iridium oxide@ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water comprises the following steps:
[0044] (1) Use 36wt% concentrated hydrochloric acid to prepare RuCl3 into a RuCl3 solution with a ruthenium concentration of 0.1g / mL. Take 10mL of 0.1g / mL RuCl3 solution and add 90mL of water to dilute it. Heat the diluted solution to 100℃, then add 1mol / L NaOH solution to it. Black flocculent precipitate gradually appears in the solution. Continue to add NaOH solution to adjust the pH to 8. Under stirring conditions, introduce 30% ozone for 1h at an ozone flow rate of 50sccm. Then add 1mol / L hydrochloric acid solution to it to adjust the pH to 7. Let it stand for 1h to obtain solution A.
[0045] (2) Under stirring, add 4 mL of IrCl4 solution with a concentration of 0.1 g / mL iridium to solution A, stir at 100°C for 1 h, and add ammonia water to adjust the pH to 12; let stand for 5 h, the solution is completely precipitated, separate the precipitate and the supernatant, and dry the precipitate at 70°C for 2.5 h to obtain a precursor;
[0046] (3) Place the precursor in a muffle furnace, heat to 500°C at a heating rate of 5°C / min, and calcine at 500°C for 5 h. After cooling, wash with 0.3 mol / L dilute hydrochloric acid and then with deionized water until there is no chloride ion in the washing solution, filter, and freeze-dry.
[0047] Comparative Example
[0048] The IrO2 catalyst material was prepared according to Example 2, except that the RuCl3 solution was replaced with the IrCl4 solution in step 1, and no additional IrCl4 solution was added in step 2, as follows:
[0049] (1) Take 10 mL of IrCl4 solution with an iridium concentration of 0.01 g / mL and add 90 mL of water to dilute it. Heat the diluted solution to 90°C, then add 1 mol / L NaOH solution to it. Black flocculent precipitates gradually appear in the solution. Continue to add NaOH solution to adjust the pH to 8. Under stirring conditions, introduce 30% ozone for 1 hour at an ozone flow rate of 50 sccm. Then add 1 mol / L hydrochloric acid solution to it to adjust the pH to 6. Let it stand for 0.5 hour to obtain solution A.
[0050] (2) Stirring at 90°C for 2 hours and adding ammonia water to adjust the pH to 12; standing for 5 hours, the liquid was completely precipitated, the precipitate and the supernatant were separated, and the precipitate was dried at 60°C for 3 hours to obtain a precursor;
[0051] (3) The precursor was placed in a muffle furnace and heated to 300°C at a heating rate of 5°C / min. The precursor was calcined at 300°C for 3 h. After cooling, the precursor was washed with 0.1 mol / L dilute hydrochloric acid and then with deionized water until there was no chloride ion in the washing solution. The precursor was filtered and freeze-dried to obtain an IrO2 catalyst.
[0052] Performance Testing
[0053] 1. SEM and TEM inspection
[0054] The iridium oxide @ ruthenium oxide composite catalyst obtained in Example 2 was subjected to SEM and TEM tests, respectively. Figure 1 and Figure 2 ,Depend on Figure 1 It can be seen that the iridium oxide @ ruthenium oxide composite catalyst particles obtained by the present invention are evenly distributed; Figure 2 It can be observed that the particle size of the iridium oxide @ ruthenium oxide composite catalyst obtained in the present invention is distributed in the range of 10-20 nm, and there is a 2-3 nm IrO2 coating layer on the surface.
[0055] 2. N2 isothermal adsorption / desorption
[0056] Figure 3 The N2 isothermal adsorption / desorption curve of the iridium oxide @ ruthenium oxide composite catalyst prepared in Example 2. It can be seen that the curve is a typical type IV characteristic isotherm, with the following features: convex in the low-pressure region, capillary condensation in the high-pressure region, non-overlapping adsorption and desorption, and the presence of a process adsorption hysteresis loop, indicating that the composite material has an obvious mesoporous distribution. The BET specific surface area of the sample is 79.7 m 2 / g.
[0057] 3. Pore size distribution
[0058] The iridium oxide @ ruthenium oxide composite catalyst prepared in Example 2 was subjected to a physicochemical adsorption test to obtain a pore size distribution. The pore size data distribution diagram is shown in FIG. Figure 4 .Depend on Figure 4 It can be seen that the pore diameter is widely distributed between 10-20 nm.
[0059] 4. Electrochemical Characterization
[0060] 4.1 Electrochemical impedance spectroscopy
[0061] The electrochemical impedance spectra of the IrO2@RuO2 composite catalyst obtained in Example 2 and the IrO2 catalyst obtained in the comparative example are shown in Figure 5 It can be seen that the charge transfer resistances of the iridium oxide @ ruthenium oxide composite catalyst obtained in Example 2 of the present invention and the IrO2 catalyst obtained in the comparative example are 6.4 Ω and 12.3 Ω, respectively, indicating that the iridium oxide @ ruthenium oxide composite catalyst with a core-shell structure has a faster charge transfer efficiency than the pure IrO2 catalyst;
[0062] 4.2 Polarization current curve
[0063] The polarization current curves of the catalysts of Examples 1-3 and Comparative Example are shown in Figure 6 ,Depend on Figure 6 It can be seen that the iridium oxide @ ruthenium oxide composite catalysts obtained in Examples 1, 2, and 3 can be used at a current density of 10 mAcm -2 When the overpotentials are 293 mV, 285 mV and 300 mV respectively, the catalytic activity is better than that of the comparative example IrO2 (316 mV) catalyst at the same current density. Among Examples 1-3, the catalyst obtained by calcining at 400 °C in Example 2 has the best catalytic activity.
[0064] 4.3 Electrochemically active surface area (ECSA)
[0065] Figure 7 The double-layer capacitance of the IrO2@RuO2 composite catalyst obtained in Example 2 and the IrO2 catalyst obtained in the comparative example ( C dl ), where IrO2@RuO2 and comparative example IrO2 catalyst C dl 31 and 18.7 mFcm respectively -2 , usually, the ECSA value of a catalyst can be obtained by C dl With oxide surface capacitance (40 μFcm -2 ) ratio, and the calculated ECSA value of IrO2@RuO2 and comparative example IrO2 is 0.078 m 2 and 0.047 m 2 , indicating that the IrO2@RuO2 composite catalyst of Example 2 of the present invention has more electrochemical active sites.
Claims
1. A method for preparing an iridium oxide @ ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water, characterized in that: The following steps are involved: (1) Prepare RuCl3 solution with concentrated hydrochloric acid, dilute with water, heat the diluted solution to 80-100°C, then add NaOH solution to adjust the pH to 8-9; introduce ozone into the solution under stirring; Then, hydrochloric acid was added thereto to adjust the pH to 6-7, and the solution was allowed to stand for 0.5-1h to obtain solution A; (2) While stirring, add iridium salt solution dropwise to solution A, continue stirring at 80-100°C for 1-2 hours and add ammonia water to adjust the pH to 12; The solution is allowed to stand until it is completely precipitated, the precipitate and the supernatant are separated, and the precipitate is dried to obtain a precursor; (3) calcining the precursor, cooling it, washing it, filtering it, and freeze-drying it; In the step (1), the concentration of ruthenium in the RuCl3 solution is 0.01-0.1 g / mL; In step (1), the concentration of ozone is 30%, the flow rate is 50 sccm, and the ozone introduction time is 0.5-1h; In the step (2), an iridium salt solution is added according to a molar ratio of iridium to ruthenium of 1:(1-5).
2. The method for preparing the iridium oxide @ ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water according to claim 1, characterized in that: The iridium salt is iridium trichloride, iridium tetrachloride, chloroiridic acid, ammonium chloroiridate, iridium acetate or potassium hexachloroiridate.
3. The method for preparing the iridium oxide @ ruthenium oxide composite catalyst suitable for acidic water electrolysis of oxygen according to claim 2, characterized in that: The drying condition in step (2) is drying at 60-70° C. for 2.5-3 h.
4. The method for preparing the iridium oxide @ ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water according to claim 3, characterized in that: The calcination conditions in step (3) are calcination at 300-700°C for 3-5h.
5. The method for preparing the iridium oxide @ ruthenium oxide composite catalyst suitable for electrolysis of oxygen in acidic water according to claim 4, characterized in that: The cleaning in step (3) is firstly cleaning with 0.1-0.5 mol / L dilute hydrochloric acid, and then cleaning with water until there is no chloride ion in the cleaning solution.
Citation Information
Patent Citations
Making method for dual-function catalyzer of recycling fuel battery
CN101087022A
Ruthenium-iridium titanium-based metal oxide electrode material based on core-shell structure, preparation method and application thereof
CN111286751A